Leadership, Organizational Culture, Work Motivation, Organizational Commitment, and Job Satisfaction as Determinants of Teacher Performance - Fadillah, M. Kharis; Dacholfany, Muhammad Ihsan; Tuala, Riyuzen Praja; Winingsih, Hesti; Marpuah, Siti (Sekolah Tinggi Agam Islam Sumatera Medan, 2024)
There are many factors that influence teacher performance, not only because of the lack of teacher competence as many are addressed at this time. This study aims to analyse the influence of leadership, organizational culture, work motivation, organizational commitment, and job satisfaction on teacher performance in State Aliyah Madrasah in Malang Raya. This study uses quantitative methods, with data collection through questionnaires and data analysis using Structural Equation Modeling. The research shows that effective leadership is characterized by the ability to create a conducive work environment. Organizational culture is influenced by integration, work motivation by achievement needs, organizational commitment by continuance commitment, job satisfaction by job fit with personality, and teacher performance by lesson planning. Good leadership helps teachers understand the institution's goals and promotes active and effective learning. Factors such as management closeness, affective commitment, and job satisfaction improve teacher performance. Recommendations are given to the Heads of State Madrasah Aliyah in Malang Raya and the Ministry of Religious Affairs to consider the importance of effective leadership in improving teacher performance. This research has implications for improving teacher performance.